The favorable effect of activating NOTCH1 receptor mutations on long-term outcome in T-ALL patients treated on the ALL-BFM 2000 protocol can be separated from FBXW7 loss of function - Kox, Corinne; Zimmermann, M.; Stanulla, M.; Leible, S.; Schrappe, M.; Ludwig, W.-D.; Köhler, Rolf; Tolle, G.; Bandapalli, Obul Reddy; Breit, S.; Muckenthaler, Martina; Kulozik, Andreas (Leukemia, 2010)
Precursor T-cell acute lymphoblastic leukemia (T-ALL) remains an important challenge in pediatric oncology. Because of the particularly poor prognosis of relapses, it is vital to identify molecular risk factors allowing early and effective treatment stratification. Activating NOTCH1 mutations signify a favorable prognosis in patients treated on ALL-BFM protocols. We have now tested if NOTCH pathway activation at different steps has similar clinical effects and if multiple mutations in this pathway function synergistically. Analysis of a validation set of 151 T-ALL patients and of the total cohort of 301 patients confirms the low relapse rate generally and the overall favorable effect of activating NOTCH1 mutations. Subgroup analysis shows that the NOTCH1 effect in ALL-BFM is restricted to patients with rapid early treatment response. Inactivation of the ubiquitin ligase FBXW7 is associated with rapid early treatment response and synergizes with NOTCH1 receptor activation. However, the effect of FBXW7 inactivation is separable from NOTCH1 activation by not synergizing with NOTCH1 mutations in predicting favorable long-term outcome, which can probably be explained by the interaction of FBXW7 with other clients. Finally, the comparison with other European protocols suggests that the NOTCH effect is treatment dependent generally and may depend on the intensity of central nervous system-directed therapy specifically.